Evaluation of Bovine Plasma Source and a Dried Milk Product on Nursery Pig Growth in a Commercial Environment - C. E. Evans; H. L. Frobose; D. W. Dean; M. D. Tokach; R. D. Goodband; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 360 barrows and gilts (PIC 359 × C29; initially 13.7 ± 3.1 lb and 19 d of age) were used in a 24-d experiment evaluating the effect of different specialty ingredients on nursery pig growth performance. This experiment was conducted in a commercial research nursery (Cooperative Research Farm Nursery; Sycamore, OH). At weaning, pigs were allotted to pens by initial BW and to one of four dietary treatments in a completely randomized design. There were 9 pens per treatment with 10 pigs per pen. Experimental diets were fed from d 0 to 10, with a common diet fed from d 10 to 24. Experimental diets were: 1) Negative control (NC); 2) NC + 5% bovine Plasma A (AP920, APC Inc.; Ankeny, IA); 3) NC + 5% bovine Plasma B (Promax; Protena S.A., Nicaragua); and 4) NC + 5% dried milk (Nutrigold; International Ingredients Corporation Inc., St. Louis, MO). All diets contained 5% fishmeal and were balanced for SID lysine, lactose, and salt. Diets were fed in pellet form. From d 0 to 10, pigs fed either Plasma A or B had greater (P<0.01) ADG and ADFI than pigs fed the NC or Nutrigold diets. Pigs fed Nutrigold had increased (P<0.01) ADG compared to pigs fed the NC diet. Also, F/G was improved (P<0.001) for pigs fed either Plasma A or B and Nutrigold diets compared to those fed the NC. During the common period (d 10 to 24), there were no differences for ADG or ADFI, although the pigs previously fed NC had improved (1.24 vs. 1.31; P<0.01) F/G compared to those previously fed Plasma A. Overall (d 0 to 24), pigs fed Plasma A and B had greater (P<0.02) ADG and ADFI than NC pigs. Pigs fed Plasma B had increased (P<0.04) ADG relative to pigs fed Nutrigold. In summary, both plasma sources increased feed intake and growth with no differences among sources. Nutrigold also improved performance compared to the NC.
Keywords: dried milk; growth; nursery pig; spray-dried bovine plasma